Normal Anatomical Features and Variations of the Vertebrobasilar Circulation and Its Branches: An Analysis with 64-Detector Row CT and 3T MR Angiographies - Akgun, Veysel (Hindawi Publishing Corporation, 2013)
Purpose. To determine the normal anatomical features and variations of the vertebrobasilar circulation and its branches in patients who underwent multidetector computed tomography (CT) or magnetic resonance (MR) angiographies of the brain. Methods. 135 patients (male, 83 and female, 52; mean age, 50.1 years) who underwent CT (n = 71) or MR (n = 64) angiographies of the vertebrobasilar vasculature for various reasons were analyzed retrospectively. The right and left distal vertebral arteries (VAs), posterior inferior cerebellar arteries (PICAs), anterior inferior cerebellar arteries (AICAs), superior cerebellar arteries (SCAs), posterior cerebral arteries (PCAs), and posterior communicating arteries (PCoAs) were analyzed individually. Results. In 24.4% of the cases (33/135) right PICA, in 19.3% of the cases (26/135) left PICA, in 17.8% of the cases (24/135) right AICA, and in 18.5% of the cases (25/135) left AICA were absent. In cases without PICA or AICA, there was a statistically significant, moderately or well-developed AICA or PICA on the same side, respectively (P < 0.001). The most common variation was isolated absence of right PICA and was seen in 17.8% of the cases. Conclusions. The anatomic features of the branches of the vertebrobasilar circulation may be different from well-known normal anatomy. CT and MR angiographies allow a precise and detailed evaluation of vertebrobasilar circulation.